The Role of Madrasah Committee in Managing Financial Management in Madrasah Aliyah Negeri - Miftahul Khoiriyah; Istikomah Istikomah; Taufik Churrahman (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
Madrasah Aliyah Negeri 2 Lamongan is a state madrasah under the auspices of the ministry of religion that gets budget funding from the government, community and self-help. The budget of the fund is expected to be on target for its use, so in the implementation of finance there needs to be community participation, namely the madrasah committee. Madrasah Aliyah Negeri 2 Lamongan Committee has a very important role in the management and implementation of financial budget programs. Through the deliberation of the budget use program that has been mutually agreed and obtained the approval of the madrasah committee, then the budget can only be disbursed to be realized as technical instructions and get supervision from various parties. The purpose of financial management of public schools through the role of the committee to be implemented effectively, transparently ,and accountably. Qualitative descriptive analysis as a research method by describing the phenomenology of the committee's role in the financial management activities of MAN 2 Lamongan. The results of this study are as follows: Madrasah committee has 4 roles in financial management, namely: 1) Advisory agency, namely the committee as a partner that gives considers to the program before the implementation of madrasah budget management activities, 2) Supporting agency that is the committee to support the implementation of budgeting funds in each madrasah education activities, 3) Controlling agency that is the committee performs its role as a supervisor in the implementation of madrasah budget 4) Executive that is as a mediator between madrasah with the community or parents of students. Madrasah must cooperate with the madrasah committee in the process of financial management in order to realize good financial management in improving the quality of madrasah education.